Build Efficient and Simple Network Operation and Maintenance of OTN - Wenxin Gong (Dianxin kexue)
The OTN technology has been widely used in metropolitan area network and big bandwidth business, but the operational complexity of OTN has been plagued by maintenance personnel, how to build efficient scheduling and simple operational OTN is a big problem to the industry. Suzhou Telecom tested and explored again and again to find out the new thinking of OTN network operations, through the establishment of OTN operational system and realized the visualization of the resource management and health analysis, carried out the routine maintenance work plan,form the network evaluation and optimization method and so on to realized the real-time monitoring and analysis of OTN, active operations, avoided the happening of the fault in advance, to build a business-centric OTN network reform mode and achieved great results.